The identity of Orthaea maculifera, with proposal of a new synonymy (Hemiptera: Heteroptera: Rhyparochromidae) - Rédei, Dávid; Zhu, Xudong; Kondorosy, Előd (Zootaxa, 2016)
Orthaea maculifera Uhler, 1861 (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae) was described by Uhler (1861) based on an unspecified number of female specimens from Hong Kong. For a long time this species remained of unknown identity and uncertain generic placement (Stål 1874, Lethierry & Severin 1894). As a result of the synonymy of the genus Orthaea Dallas, 1852 with Pachybrachius Hahn, 1826 proposed by Barber (1939) (not accepted by Harrington (1980) and subsequent workers), Slater (1964) listed the species within the genus Pachybrachius. Although the species has still been regarded as of unknown identity (Zheng & Zou 1981), this generic placement has been followed by subsequent authors (Péricart 2001).